2000
DOI: 10.1084/jem.192.6.823
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (Il)-4 Is a Major Regulatory Cytokine Governing Bioactive IL-12 Production by Mouse and Human Dendritic Cells

Abstract: Interleukin (IL)-12 may be secreted as a bioactive T helper type 1 (Th1) cell–inducing heterodimer, as a monomer, or as an antagonistic homodimer. We analyzed the IL-12 produced by mouse splenic dendritic cells (DCs), human thymic DCs, and cultured human monocyte-derived DCs. IL-12 production required both a microbial or T cell–derived stimulus and an appropriate cytokine milieu. The different IL-12 forms were differentially regulated by the cytokines present rather than the stimulus used. IL-4 alone or togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
272
2
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(302 citation statements)
references
References 55 publications
27
272
2
1
Order By: Relevance
“…In contrast, it has been reported previously that CD8 T cell-mediated IL-12p70 production could occur without stimulation from pathogenderived signals [11,14,15]. A possible reason is that GM-CSFand IL-4-generated DC used in those studies have a greater propensity to produce IL-12p70 than splenic DC [27,29]. We argue that our study better reflects events that may occur with splenic resident DC in vivo.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In contrast, it has been reported previously that CD8 T cell-mediated IL-12p70 production could occur without stimulation from pathogenderived signals [11,14,15]. A possible reason is that GM-CSFand IL-4-generated DC used in those studies have a greater propensity to produce IL-12p70 than splenic DC [27,29]. We argue that our study better reflects events that may occur with splenic resident DC in vivo.…”
Section: Discussionmentioning
confidence: 63%
“…IFN-c, GM-CSF, TNF-a and IL-4 are T cell-derived cytokines thought to be involved in promoting IL-12p70 production by DC [14,15,[26][27][28]. We investigated whether these factors were involved in our system.…”
Section: Cd8 T Cell-mediated Il-12p70 Production Is Dependent On Ifn-cmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 IL-4 can enhance the production of IL-12 by DC and has been confirmed to play roles in the antitumor response. 8,11 Immature DC undergo a maturation process after they encounter antigens, and subsequently migrate to lymphoid tissue to prime naive T cells. 12,13 Induction of effective antitumor response requires DC to present tumor antigen, 14 but tumor cells often have limited expression of MHC antigens and costimulatory molecules, [15][16][17] and also tumor cells can produce immune inhibitory factors that inhibit DC maturation and migration.…”
Section: Activated DC To Produce High Levels Of Il-12 Furthermore Amentioning
confidence: 99%
“…Sideby-side comparisons concluded that GM-CSF mainly differentiates monocyte-derived DCs and Flt3L differentiates the equivalents of resident CD8 1 DCs [16]. Although exogenous GM-CSF seems dispensable for the development of CD8 1 DCs [16], GM-CSF has been used in the cultures of resident DCs including CD8 1 DCs for functional assays to promote DC survival [17]. It was not known whether GM-CSF is required for the potentiation of function of CD8 1 DCs in vivo; nor what the molecular target of GM-CSF is.…”
Section: Introductionmentioning
confidence: 99%